MOTIVASI INTERNAL DAN EKSTERNAL PEMAKAIAN GIGI TIRUAN PADA PAGUYUBAN LANSIA “SEHAT BUGAR” POLTEKKES SEMARANG - Sukini Sukini; Betty Saptiwi; Wahyu Jati Diyah Utami; Endra Nastiti Donasari (Jurnal Kesehatan Gigi, 2015)
TITLEInternal and external motivation of denture wearing in elderly community “sehat bugar” of Poltekes SemarangABSTRACTTooth damage like carries, even when the carries is still on process or when it cannot be maintained and should be removed, will cause some health problems if it is ignored. Loosing teeth in long term period will lead to the changes of teeth arrangement so the contact will be imperfect. Other negative impacts that are caused by caries are the decrease of speaking function and aesthetic functions.Although most people loose their teeth, either by dental caries process or by other causes, not all of them immediately applying an artificial teeth or wear dentures. The awareness to make the denture is influenced by factors both internal and external. Internal factors include the self-perception, interests, needs and expectations. External factors consist of the support of family, environment, health care facilities, benefits and rewards received. Motivations is the factor that drives or moves a person to behave and lead towards a specific goal.This research aims to observe the motivation of denture-using on Poltekkes Semarang’s elders community “Sehat Bugar" Poltekkes. This observation research was conducted in the August until the early of September 2014, whereas the data were processed in September 2014. The sample used in this research is the total samples of 67 subjects in order to get a better representative.The results of the Chi Square correlation analysis shows there is significant relationship between Internal motivation and the use of denture with 0.012 (p 0.05) of sig value and there was no relationship between external motivation and the use of denture with 0.604 (p 0.05) of sig value. Keywords      : Internal motivation,External motivation, denture